The SARS-CoV2 and mitochondria: the impact on cell fate: SARS-CoV2 and mitochondria - Madeddu, Eleonora; Maniga, Barbara; Zaffanello, Marco; Fanos, Vassilios; Marcialis, Antonietta (Acta Biomedica Atenei Parmensis, 2022)
Coronavirus infection causes endoplasmic reticulum stress inside the cells, which inhibits protein folding. Prolonged endoplasmic reticulum stress causes an apoptotic process of unfolded protein response-induced cell death. Endoplasmic reticulum stress rapidly induces the activation of mTORC1, responsible for the induction of the IRE1-JNK pathway. IRE1-JNK stands out for its dual nature: pro-apoptotic in the first stage of infection, anti-apoptotic in persistently infected cells. Once penetrated the cells, the virus can deflect the mitochondrial function by implementing both waterfalls pro-apoptotic and anti-apoptotic response. The virus prevents, through Open Reading Frame 9b (ORF-9b) interacting with mitochondria, the response of the type I interferon of the cells affected by the infection and is fundamental for generating an antiviral cellular state. ORF-9b has effects on mitochondrial dynamics, inducing fusion and autophagy and promoting cell survival. The recognition of ORF-9b has made it possible to identify it as a molecular target of some existing potentially effective drugs (Midostaurin and Ruxolitinib). Other drugs, with the same target, are currently being tested. Given the great importance of mitochondria in virus-host interaction, in-depth knowledge of the actors and pathways involved is essential to continue developing new therapeutic strategies against SARS CoV2.